Job Satisfaction Among Auditors in Slovenia: An Empirical Study - Majcan, Ana; Kolar, Iztok (Naše gospodarstvo/Our economy, 2025)
This study examines job satisfaction among auditors (CPAs) in Slovenia, and its relationship with professional age, decision-making level, gender, and audit firm size. A modified Job Descriptive Index (JDI) questionnaire was administered to auditors in Slovenija. Data were analysed using ANOVA, Kruskal–Wallis H, and Mann–Whitney U tests. Overall, job satisfaction is high, about 75% all possible points on JDI measurement scale. No statistically significant differences were identified across professional age, decision-making level, gender, or audit firm size, indicating a homogeneous satisfaction pattern. Cross-sectional, self-reported data from a single country may limit generalisability. The results highlight the need for audit firms to support well-being, clarify career paths, and strengthen perceived autonomy to retain and attract young auditors. This is one of the first empirical studies of Slovenian auditors’ job satisfaction, using the JDI framework and several demographic and organisational variables.